Α‐Synuclein activates innate immunity but suppresses interferon‐γ expression in murine astrocytes. (22nd June 2018) - Wang, Jintang; Chen, Zheng; Walston, Jeremy D.; Gao, Peisong; Gao, Maolong; Leng, Sean X.
Abstract: Glial activation and neuroinflammation contribute to pathogenesis of neurodegenerative diseases, linked to neuron loss and dysfunction. α‐Synuclein (α‐syn), as a metabolite of neuron, can induce microglia activation to trigger innate immune response. However, whether α‐syn, as well as its mutants (A53T, A30P, and E46K), induces astrocyte activation and inflammatory response is not fully elucidated. In this study, we used A53T mutant and wild‐type α‐syns to stimulate primary astrocytes in dose‐ and time‐dependent manners (0.5, 2, 8, and 20 μg/ml for 24 hr or 3, 12, 24, and 48 hr at 2 μg/ml), and evaluated activation of several canonical inflammatory pathway components. The results showed that A53T mutant or wild‐type α‐syn significantly upregulated mRNA expression of toll‐like receptor (TLR)2, TLR3, nuclear factor‐κB and interleukin (IL)‐1β, displaying a pattern of positive dose–effect correlation or negative time–effect correlation. Such upregulation was confirmed at protein levels of TLR2 (at 20 μg/ml), TLR3 (at most doses), and IL‐1β (at 3 hr) by western blotting. Blockage of TLR2 other than TLR4 inhibited TLR3 and IL‐1β mRNA expressions. By contrast, interferon (IFN)‐γ was significantly downregulated at mRNA, protein, and protein release levels, especially at high concentrations of α‐syns or early time‐points. These findings indicate that α‐syn was a TLRs‐mediated immunogenic agent (A53T mutant stronger than wild‐type α‐syn). The stimulation patterns suggest that persistent release and accumulation of α‐syn is required for the maintenance of innate immunity activation, and IFN‐γ expression inhibition by α‐syn suggests a novel immune molecule interaction mechanism underlying pathogenesis of neurodegenerative diseases. Abstract : α‐Synuclein (α‐syn, A53T mutant or wild‐type) stimulated TLR2 and TLR3, as well as TLR1 or TLR4, to activate inflammatory pathway by upregulating expression of NF‐κB, IL‐1β, and IFN‐β, whereas IFN‐γ expression was significantly downregulated. Blockage of TLR2 other than TLR4 suppressed expression of TLR3 and IL‐1β. These data indicate a potential interaction mechanism of inflammatory factors in pathogenesis of neurodegenerative diseases.